Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00264-012-1601-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density changes of the proximal tibia after revision total knee arthroplasty. A randomised study with the use of porous tantalum metaphyseal cones

Abstract: Purpose Forty patients were enrolled in a prospective randomised study using conventional method or "Trabecular Metal Cone" (TM Cone) (Zimmer inc., Warsaw, USA) for reconstruction of bone loss of the proximal tibia during revision total knee arthroplasty (rTKA). The aim was to evaluate changes in bone mineral density (BMD) at the proximal tibia. Material and methods Thirty-six patients [median 67 years (range: 40-85 years)] received rTKA with NexGen® (Zimmer Warsaw, USA) revision system. Knee Society´s Knee Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
2
29
1
Order By: Relevance
“…Regarding rTKAs, our data suggest that in the distal femur and proximal tibia a bone resorption is consistent, while no substantial modification is revealed at the tip of femoral stems (ROI 4). This is significantly different from what reported in a previous study, in which an increase in the femur at the tip of stems has been found (34). By using a high press-fit stem for the tibial component in rTKA we have observed a bone apposition at 3 and 6 months, and a lesser resorption at 24 months compared to the low press-fit implantation (53).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Regarding rTKAs, our data suggest that in the distal femur and proximal tibia a bone resorption is consistent, while no substantial modification is revealed at the tip of femoral stems (ROI 4). This is significantly different from what reported in a previous study, in which an increase in the femur at the tip of stems has been found (34). By using a high press-fit stem for the tibial component in rTKA we have observed a bone apposition at 3 and 6 months, and a lesser resorption at 24 months compared to the low press-fit implantation (53).…”
Section: Discussioncontrasting
confidence: 56%
“…By using a high press-fit stem for the tibial component in rTKA we have observed a bone apposition at 3 and 6 months, and a lesser resorption at 24 months compared to the low press-fit implantation (53). Bone remodelling activity in THA and in rTKA is a process that seems to intensively develop during the first year after surgery, then reducing in the second year (32,34,47,(54)(55)(56)(57). Such observations, associated to other reported in literature have aroused a great interest in the proposal of bone metabolic therapies to improve the quality of osseointegration, particularly in the first months after an arthroplasty (12,57,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 There may be a lower rate of infection with these cones compared with bulk allografts, but this has not been conclusively proven. As opposed to allograft bone, the metaphyseal cones will not have a possibility of late bone resorption and possible fracture.…”
Section: Methodsmentioning
confidence: 96%
“…Because of the porosity of this material, osseointegration and penetration of the cement is improved [3]. Metaphyseal filling provides more balanced transfer of peripheral loads, reducing the risk of repeat loosening [4]. Meneghini et al [5] described the use of a porous tantalum cone for tibial bone defects during revision TKA.…”
Section: Introductionmentioning
confidence: 98%